Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Karyawan di Fox Hotel Pekanbaru - Maryantina Maryantina; Sri Febdarina; Lisa Santiae; Lisa Lestari; Sefrona Syaiful (Yayasan Literasi Sains Indonesia, 2025)
Employee performance is a crucial element in the success of hotel industry operations that are increasingly competitive. The phenomenon of low employee performance in the hospitality sector is often associated with the lack of effective training programs and work motivation. This study aims to determine the effect of training and work motivation on employee performance simultaneously and partially at FOX Hotel Pekanbaru. This study uses quantitative methods with data collection techniques in the form of observation, interviews, questionnaires and documentation. the sample of this study was 77 people consisting of all FOX Hotel employees who were taken by saturated sampling. the data were analyzed descriptively to describe the research data, and multiple linear regression analysis to test the effect of independent variables on one dependent variable. The results of this study indicate that the simultaneous test of training and work motivation has a significant effect on employee performance at FOX Hotel Pekanbaru which is indicated by the Fcount > Ftable value of 14,262 > 3. 122 means that training and work motivation have a significant effect on employee performance at FOX Hotel Pekanbaru, and the amount of influence is shown by the results of the determinant test (R2) or R Square 0.729 means that the effect of training and work motivation on employee performance FOX Hotel Pekanbaru is 72.9% while the remaining 27.1% is influenced by other factors outside of this research variable such as job satisfaction, work ability, work environment, and compensation. While the effect of training partially indicated by the value of tcount > ttable which is equal to 3.373 > 1.666, partially significant effect on employee performance at FOX Hotel Pekanbaru. Based on the findings of this study, FOX Hotel Pekanbaru management is advised to prioritize the implementation of recognition systems, career development pathways, and employee empowerment programs as key strategies for improving performance.